2020
DOI: 10.1007/s10549-020-05865-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fibroblast growth factor receptor 1 (FGFR1) amplification on the prognosis of breast cancer patients

Abstract: Purpose Various aberrations in the fibroblast growth factor receptor genes FGFR1, FGFR2, and FGFR3 are found in different cancers, including breast cancer (BC). This study analyzed the impact of FGFR amplification on the BC prognosis. Methods The study included 894 BC patients. The amplification rates of FGFR1, FGFR2, and FGFR3 were evaluated on tissue microarrays using fluorescence in situ hybridization (FISH). Associations between these parameters and prognosis were analyzed using multivariate Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…ZNF703 was found a common luminal B breast cancer oncogene ( 27 ). FGFR1 amplification was positively associated with luminal B breast cancer ( 28 ). In this work, FGFR1 mutations were either amplification (83.3%) or gene fusion (16.7%).…”
Section: Discussionmentioning
confidence: 99%
“…ZNF703 was found a common luminal B breast cancer oncogene ( 27 ). FGFR1 amplification was positively associated with luminal B breast cancer ( 28 ). In this work, FGFR1 mutations were either amplification (83.3%) or gene fusion (16.7%).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR frequent overexpression and/or hyperactivation in breast carcinomas play an active role in facilitating brain-specific metastatic spread [ 49 , 50 ]. In addition, FGFR aberrations increase the risk of brain metastases and predict poor prognosis in metastatic breast cancer patients [ 51 , 52 ]. We found that PNSA distinctly suppressed the protein levels of EGFR and FGFR, and subsequently inhibiting down-streaming signaling pathway with reduction of P-ERK, P-STAT3, and P-AKT.…”
Section: Discussionmentioning
confidence: 99%
“…As previously described, corresponding tissue microarrays (TMAs) were created for all patients in the BBCC cohort for whom paraffin blocks were available [29]. As part of the initial documentation of the disease, the tumor status was documented in accordance with the TNM classification.…”
Section: Histopathological Assessmentmentioning
confidence: 99%